THE EVALUATION OF THE CAUSES OF RETAINING WALL STRUCTURE FAILURE AT A RIVER BASED ON SNI 2847:2013 - Tri Handayani; Sudarmadi Sudarmadi (Majalah Ilmiah Pengkajian Industri, 2020)
In this paper, the application of SNI 2847:2013 in the evaluation of the case of a retaining wall failure is presented. The method is the analytical retaining wall evaluation, which consisted of visual inspection in the field, depth measurement of pile and sheet pile, and the quality test of concrete material. The data were used as input in structure modeling using Finite Element Method (FEM) software to calculate each structural member's required strength (Ru). The calculation was done to obtain the design strength (ØRn) of the structural member. The retaining wall is considered safe if its design strength is greater than or equal to the required strength or ØRn ? Ru. If this condition cannot be fulfilled, the retaining wall is considered failed, and then the causes of failure would be performed. The result showed that the depth of the pile and sheet pile is less than the required minimum depth, and concrete quality is below the specification mentioned in the as-built drawing data. According to structural analysis and calculation of site investigation data, it could be known that the causes of retaining wall failure are the design strength is smaller than the required strength and the vertical moment due to its self-weight is much smaller than the horizontal moment due to soil and water pressure, so it causes the structural sliding. Keywords: Retaining Wall Failure; Retaining Wall Evaluation; Required Strength; Design Strength; Sliding